Classification of Blood Culture Isolates Into Contaminants and Pathogens on the Basis of Clinical and Laboratory Data. Issue 5 (May 2016) - Hossain, Belal; Weber, Martin W.; Hamer, Davidson H.; Hibberd, Patricia L.; Ahmed, A. S. M. Nawshad Uddin; Marzan, Mahfuza; Islam, Maksuda; Connor, Nicholas E.; Islam, Mohammad Shahidul; Zaidi, Anita K.; Baqui, Abdullah H.; Bhutta, Zulfiqar A.; et al.
Abstract : The multisite community-based study, Aetiology of Neonatal Infection in South Asia (ANISA), uses blood culture as the gold standard for identifying the etiology of neonatal infection. Considering the importance of this age-old diagnostic tool and the risk of contamination, ANISA has employed rigorous measures to prevent contamination at all stages of blood collection, processing and culture. Because contamination may still occur, an independent expert group evaluates the routinely collected clinical and laboratory data to determine whether a blood culture isolate is a contaminant or a true pathogen. This article describes the methodology used by ANISA to determine whether a blood culture isolate is likely to be a true pathogen or a contaminant in neonatal sepsis.